2021
DOI: 10.1177/10556656211025189
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Clinical Practice Guidelines for Oral Health in Children With Cleft Lip and Palate

Abstract: Objective: Clinical practice guidelines (CPGs) exist to present recommendations and policies aimed at optimizing the oral health of children and adolescents born with cleft lip and/or palate. The aim of this review is to identify and assess the scope, quality, adequacy, and consistency of CPGs related to oral health in children and adolescents with clefts, along with reporting any differences and shortcomings. Methods: A systematic review of the literature of CPGs following Preferred Reporting Items for System… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…Based on the results, the achievement of a consensus with regard to cleft care across Europe remains suboptimal and challenging. These results are in agreement with a recent systematic review that concluded a lack of integrated high-quality clinical practice guidelines that can be used as universal guidelines in cleft treatment [ 29 ]. Therefore, there is a need for better coordination between clinicians and national and international regulatory bodies and centers.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the results, the achievement of a consensus with regard to cleft care across Europe remains suboptimal and challenging. These results are in agreement with a recent systematic review that concluded a lack of integrated high-quality clinical practice guidelines that can be used as universal guidelines in cleft treatment [ 29 ]. Therefore, there is a need for better coordination between clinicians and national and international regulatory bodies and centers.…”
Section: Discussionsupporting
confidence: 92%
“…This is a background question on the organization of care, which is difficult to translate into a search question for a systematic review. A recently published systematic review of CPGs for oral health care in children with clefts identified seven, but none of them were rated as high quality for “Rigor of Development” [ 81 ]. This shows that there is no high-quality evidence on which to base a recommendation for organization of care.…”
Section: Resultsmentioning
confidence: 99%
“…The strengths of the current review are (1) the appraisal was performed by a specialised clinical team of paediatric dentists, oral radiologist, oral surgeon, periodontist, clinician researchers and experts from universities in India, Australia and the United Arab Emirates, (2) the other advantages include the use of internationally accepted, rigorously structured and validated CPGs appraisal tools such as the AGREE II and AGREE REX, (3) the appraisal of each CPGs by four appraisers including three clinical topic experts and two members from the Guidelines International Network (GIN) who had undergone training in guideline development and had published previous similar studies regarding the management of cleft lip and palate, 42 and (4) the reviewers carried out a comprehensive search within several core databases as well as ministries of health and various guideline related databases.…”
Section: Discussionmentioning
confidence: 99%